The Analysis of Polyethylene Hip Joint Endoprostheses Strength Parameters Changes after Use inside the Human Body - Arkadiusz Szarek (MDPI AG, 2021)
The influence of dynamic loads resulting from human motor activity and electrocorrosion inside the human body on the strength parameters of artificial joint elements has not yet been investigated. Hip joint arthroplasty is the most common surgical procedure in the world that allows doctors to remove pain and restore motor skills in people with severe hip diseases, after accidents, and in the elderly. Based on the reports, this article assesses changes in the number of implanted endoprostheses in the years 2005–2019 and determines the trends and estimated changes in the number of implanted hip prostheses in the following decades. The study assesses changes in selected strength parameters of UHMW-PE polyethylene inserts of hip joint endoprostheses during their use in the human body. The research was carried out on appropriately collected samples from UHMW-PE cups removed from the human body with a known history and lifetime from 4 to 10 years. Patients’ body weight ranged from 735 [N] to 820 [N], and the declared physical activity was similar in the entire research group. As part of the research, the values of changes in dynamic modules and the mechanical loss coefficient were determined in relation to the share of the crystalline and amorphous phases of artificial UHMW-PE cups, removed from the human body after different periods of exploitation under similar operating conditions. The analysis of selected strength parameters was performed at a temperature of 40 °C, which corresponds to the working conditions inside the human body. On the basis of numerical studies, the influence of changes in material parameters on the deformation of the artificial acetabulum during the patient’s motor activity, which is one of the causes of fatigue destruction, was determined.